Hypoglykemie u nediabetiků - Škrha, Jan (Vnitrni lekarstvi, 2020)
Hypoglycemia is a rather frequent complication of diabetes treatment, however it can occur also in non-diabetic patients. The article presents a brief differential diagnosis of hypoglycemia in non-diabetic patients.
Keywords: Insulinoma; Diagnosis, Differential; postprandial hypoglycemia; Diabetes Mellitus, Type 2; Pancreatic Neoplasms; diferenciální diagnóza; lidé; hypoglycemia; inzulinom; hypoglykemie; type 2 diabetes; nádory slinivky břišní; diabetes mellitus 2. typu; insulinoma; Hypoglycemia; Humans